President’s Message - McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2009)
As I write my first message, as ORNAC President, I am cognizant of the past efforts of many perioperative nurses that have guided ORNAC toward today’s successful association. In the second edition of the Canadian Operating Room Nursing Journal (June 1983) Val Shirreff’s message as the first ORNAC President outlined the responsibilities of the membership: “The creation of this association, however, is only a beginning, albeit, an historical and propitious one. Now, it must be nurtured through its formative stages, sustained, and nourished until it has a strong and vibrant past on which to grow upon. In other words, as operating room nurses, it is yours and my task, together and as members of a professional fraternity, to guide it to maturity.”1